Who Left the Dog Out (of the History)? - : Capnocytophage Canimorus Baceteremia Induced Sepsis - Holtzapple, Zachary (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.